(untitled) (New York, 1995)
This work sets out to provide the primary care physician with an all-encompassing review of office-based management of the full spectrum of obstetric and gynaecologic disorders and conditions presented by the female patient.
Keywords: Women's health services,Dịch vụ y tế phụ nữ